Effects of layup sequences on stresses of thick composite cantilever tubes. (4th May 2017) - Yazdani Sarvestani, Hamidreza
Abstract : In this study, a new simple-input displacement-based method is used to study effects of layup sequences on stresses, strains, and deformations of thick laminated orthotropic cantilever straight tubes under transverse loading. Three-dimensional stress distributions are obtained based on the most general displacement field of elasticity. A layer-wise theory which includes the full three-dimensional constitutive relations is used. A non-dimensional simple coefficient is introduced to compare interlaminar radial stresses of different layup sequences. Finally, some design guidelines are proposed to consider effects of layup sequences of laminated thick composite tubes subjected to shearing load.